TINGKAT PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN FISIK DESA - Ainur Rofiq; Afifudin Afifudin (Department of Islamic Community Development, Faculty of Dakwah,Universitas Islam Ibrahimy Banyuwangi, 2023)
Community participation in the physical development of the village in Gumuk Village, Licin District, Banyuwangi Regency, is a crucial factor in achieving the success of the development program. Community participation can be seen from their participation in various stages of development, from planning to evaluation. This study uses qualitative research types, observation, interview, and documentation methods are used to collect community participation data, data analysts are used to use Huberman miles data analysis which includes data condensation, presenting data, and drawing conclusions or verification by checking the wetness of source triangulation data. The results showed that community participation was carried out through socialization, data collection, identification of potentials and problems, and active participation in the implementation of physical development. People in Gumuk Village contribute energy, property, money, and expertise voluntarily in making talud, culverts, roads, and buildings. This community participation reflects a shared awareness and interest in advancing the village.